Efektivitas Manajemen Syariah dalam Meningkatkan Kinerja Lembaga Keuangan Islam - Akbar, Muh Asy'ari; Akbar, Firman Muhammad Abdurrohman (Kopertais Wilayah I DKI Jakarta dan Banten, 2024)
This study aims to examine the effectiveness of Sharia management in enhancing the performance of Islamic financial institutions. Utilizing qualitative methods and a literature review approach, this research delves into how the implementation of human resource management (HRM) and oversight by the Sharia Supervisory Board (SSB) contribute to the improved performance of Islamic financial institutions. The findings indicate that HRM in Islamic financial institutions, which includes recruitment, training, performance evaluation, and incentive systems, not only focuses on achieving financial targets but also emphasizes the importance of compliance with Sharia principles. Effective HRM implementation has been proven to enhance service quality, customer satisfaction, and adherence to Sharia principles, all of which positively impact the institution's performance. On the other hand, the effectiveness of oversight by the SSB in ensuring Islamic financial institutions' compliance with Sharia principles is found to be a critical factor in determining financial performance and strengthening customer trust. The SSB plays a vital role in auditing and evaluating the products and operations of the institution to ensure there are no deviations from Sharia law that could damage the institution's integrity or reputation. This research confirms that effective Sharia management and stringent oversight by the SSB not only support financial growth but also strengthen the ethical and moral foundations of Islamic financial institutions, which are crucial in maintaining customer trust and loyalty. Therefore, strict implementation of Sharia principles and effective oversight by the SSB are key to the sustainability and success of Islamic financial institutions in the long term.